MiR‐301b and NR3C2 co‐regulate cells malignant properties and have the potential to be independent prognostic factors in breast cancer. Issue 2 (15th October 2020) - Peng, Yun; Xi, Xun; Li, Juntao; Ni, Jun; Yang, Hongbiao; Wen, Changyong; Wen, Meiling
Abstract: This study intends to address the function of miR‐301b/nuclear receptor subfamily 3 group C member 2 (NR3C2) in breast cancer. The Cancer Genome Atlas database was processed to investigate the expression of miR‐301b/NR3C2 in breast cancer samples, as well as the relationship between their expression and the prognosis of the patients. Cox regression analysis was performed to determine whether miR‐301b/NR3C2 was an independent predictor of the patient's prognosis. Associations between miR‐301b and NR3C2 were analyzed by prediction website, dual‐luciferase assay, and Pearson correlation coefficient. Quantitative polymerase chain reaction and Western blot analyses were implemented to detect gene expression. The relevant biological characteristics of MCF7 and BCAP‐37 cells were tested by cell counting kit‐8, colony formation, and transwell assays. Lower expression of NR3C2, which was closely related to the bad prognosis of breast cancer patients, was presented in breast cancer samples and can be used as an independent predictor. miR‐301b, as an upstream regulator of NR3C2, was highly expressed in breast cancer samples and can be used as an independent predictor as well. Notably, a higher level of miR‐301b and lower level of NR3C2 were related to the reduced overall survival in patients with breast cancer. The proliferative and migratory behaviors of cells were elevated or blocked after overexpression of miR‐301b or NR3C2, respectively. However, the above situation was attenuated after together upregulation of miR‐301b and NR3C2. The present data afforded evidence that miR‐301b may be a tumor‐promoting miRNA in breast cancer, and that miR‐301b/NR3C2 axis mediated tumor development from cell proliferation and migration.